Do Judges Hate Speculators? - Lars Hornuf; Lars Klöhn (Center for Economic Studies and ifo Institute (CESifo), 2018)
Historically, people have often expressed negative feelings toward speculators, a sentiment that might have even been reinforced since the latest financial crisis, during which taxpayer money was warranted or spent to bail out reckless investors. In this paper, we conjecture that judges may also have anti-speculator sentiment, which might affect their professional decision making. We asked 123 professional lawyers and 247 law students in Germany this question, and they clearly predicted that judges would have an anti-speculator bias. However, in an actual behavioral study, 185 judges did not exhibit such bias. In another sample of 170 professional lawyers, we found weak support for an anti-speculator bias. This evidence suggests that an independent audience may actually perceive unbiased judgments as biased. While the literature usually suggests that a communication problem exists between lawyers and non-lawyers (i.e. between judges and the general public), we find that this problem can also exist within the legal community.
Keywords: C90; K41; 330; speculator bias; judges; experimental law and economics